Barriers and facilitators to self-management in people with back-related leg pain: a qualitative secondary analysis - Anna-Marie L. Ziegler; Don Thorpe; Douglas Kennedy; Craig Schulz; Stacie A. Salsbury; Gert Bronfort; Roni Evans (Chiropractic & Manual Therapies)
Abstract Background Back related leg pain (BRLP) is a problematic subset of low back pain, leading to greater pain, loss of function and health related care costs. While evidence suggests self-management is effective, patient implementation can be sub-optimal. The purpose of this study is to identify barriers and facilitators to self-management for persons experiencing BRLP within the context of a controlled clinical trial and to map these to theory-informed intervention elements that can be addressed by front-line healthcare providers, informing the design and implementation of future theory-driven self-management interventions for this population. Methods This study was a qualitative secondary analysis of a 2-site, pragmatic, parallel group, randomized clinical trial (participants enrolled 2007–10) of spinal manipulative therapy (SMT) and home exercise and advice (HEA) compared to HEA alone for persons with subacute or chronic BRLP. We used deductive and inductive content analysis, to describe self-management facilitators and barriers among trial participants, map these to behavior change elements in the Behavior Change Wheel (BCW) Framework, and identify potentially modifiable, theory-intervention elements which may be addressed with guidance by healthcare providers. Baseline characteristics of participants were descriptively analyzed using SAS (University Edition). Results Of 40 participants, the majority identified as white (n = 24, 85%) and of non-Hispanic or Latino ethnicity (n = 38, 95%). Average participant age was 57 years old (range 29–80). Frequent facilitators included ease of exercises, knowing how to manage condition, atmosphere created by staff, therapeutic alliance, effectiveness of exercises or treatment, goal of reducing pain, and intentions of continuing exercises. Frequent barriers included time constraints, pain, and lacking confidence in treatment. Barriers were mapped to all 9 Intervention Functions, most common being modelling and education. Frequently identified Behavior Change Techniques included information, feedback, self-monitoring, graded tasks, restructuring, social support, goal setting, reviewing goals, and action planning. Conclusion This study identified barriers and facilitators to engaging in self-management for participants in a pragmatic, randomized clinical trial. A rigorous systematic intervention mapping process utilizing the BCW was used for describing what participants need and how their needs may be met. These findings may support the design of future self-management interventions for persons experiencing BRLP.